Intranasal immunization with protective antigen of Bacillus anthracis induces a long-term immunological memory response. Issue 2 (October 2015) - Woo, Sun-Je; Kang, Seok-Seong; Park, Sung-Moo; Yang, Jae Seung; Song, Man Ki; Yun, Cheol-Heui; Han, Seung Hyun
Highlights: Intranasal immunization with rPA induces mucosal and systemic immune responses. PA-specific memory B cells are increased in mucosal and systemic compartments. Effector memory CD4 + T cells are remarkably generated in the lung. Th1- and Th17-type cytokines are selectively increased in the lung. Abstract: Although intranasal vaccination has been shown to be effective for the protection against inhalational anthrax, establishment of long-term immunity has yet to be achieved. Here, we investigated whether intranasal immunization with recombinant protective antigen (rPA) of Bacillus anthracis induces immunological memory responses in the mucosal and systemic compartments. Intranasal immunization with rPA plus cholera toxin (CT) sustained PA-specific antibody responses for 6 months in lung, nasal washes, and vaginal washes as well as serum. A significant induction of PA-specific memory B cells was observed in spleen, cervical lymph nodes (CLNs) and lung after booster immunization. Furthermore, intranasal immunization with rPA plus CT remarkably generated effector memory CD4 + T cells in the lung. PA-specific CD4 + T cells preferentially increased the expression of Th1- and Th17-type cytokines in lung, but not in spleen or CLNs. Collectively, the intranasal immunization with rPA plus CT promoted immunologic memory responses in the mucosal and systemic compartments, providing long-term immunity.